About denial in Asháninka (Arawak) - Vílchez Jiménez, Elsa (2012)
This articule deals with the most used negation forms of ashaninka (Arawakan) language spoken in Ponchoni, a community located in the Gran Pajonal zone of the Peruvian Amazonia. We discuss on negation forms such as: tee, eero, kaari, teekatsi, tekatsite and teekirata.